2013
DOI: 10.1681/asn.2012080771
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between PLA2R1 and HLA-DQA1 Variants Associates with Anti-PLA2R Antibodies and Membranous Nephropathy

Abstract: Risk alleles at genome loci containing phospholipase A2 receptor 1 (PLA2R1) and HLA-DQA1 closely associate with idiopathic membranous nephropathy (IMN) in the European population, but it is unknown whether a similar association exists in the Chinese population and whether high-risk alleles promote the development of anti-PLA2R antibodies. Here, we genotyped 2132 Chinese individuals, including 1112 patients with IMN and 1020 healthy controls, for three single nucleotide polymorphisms (SNPs) within PLA2R1 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
129
2
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 20 publications
(23 reference statements)
11
129
2
12
Order By: Relevance
“…Our study provides additional support to the previously found associations between IMN and common coding and noncoding variants within PLA2R1 and HLA-DQA1 genes (14,18,19,29). Interestingly, the disease-associated genotype of PLA2R1 (rs4664308) is the common genotype, which was previously reported (14,30). These associations with relatively common variants, although IMN is a rare disease, raised the hypothesis that the confluence of relatively common polymorphisms in these genes may result in a rare haplotype that confers susceptibility to IMN (29,31).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study provides additional support to the previously found associations between IMN and common coding and noncoding variants within PLA2R1 and HLA-DQA1 genes (14,18,19,29). Interestingly, the disease-associated genotype of PLA2R1 (rs4664308) is the common genotype, which was previously reported (14,30). These associations with relatively common variants, although IMN is a rare disease, raised the hypothesis that the confluence of relatively common polymorphisms in these genes may result in a rare haplotype that confers susceptibility to IMN (29,31).…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Lv et al (30) found that 73% of individuals carrying these IMN susceptibility genotypes had anti-PLA2R antibodies, whereas these antibodies were absent in all carriers of the protective genotypes. In our cohort, immunosuppressive therapy was more effective in patients carrying the IMN susceptibility genotype combination, likely by decreasing anti-PLA2R levels.…”
Section: Discussionmentioning
confidence: 99%
“…shown that, the antibody titres disappear with remission and reappear with disease relapses (8,13,14,17,18,(27)(28)(29)(30)(31)(32). Moreover, anti-PLA 2 R levels were in direct proportion to proteinuria and serum albumin levels.…”
Section: Discussionmentioning
confidence: 91%
“…9 All three SNPs within PLA2R1 were highly associated with MN, and the strongest signal emerged from the same SNP (rs4664308) identified in the European GWAS. The HLA-DQA1 SNP (rs2187668) also showed association with MN, whereas two other HLA-located SNPs showed no such association with disease.…”
mentioning
confidence: 80%